Influence of Nitrogen, Calcium and Nano-Fertilizer on Strawberry (Fragaria × ananassa Duch.) Fruit Inner and Outer Quality - Nika Cvelbar Weber; Darinka Koron; Jerneja Jakopič; Robert Veberič; Metka Hudina; Helena Baša Česnik (Agronomy, 2021)
The production system, especially fertilisation has an important effect on yield and quality of strawberries. In the present study, plants were fertilized with different doses of nitrogen (0–100% recommended doses), calcium chelate, as well as nano fertilizer Lithovit. Strawberry cultivar ‘Clery’ yield and quality parameters (fruit color and firmness) including nutritional indicators (total soluble solids, sugars, organic acids, phenolic and volatile compounds) were monitored. Volatiles were identified and monitored using headspace solid phase microextraction and analysed using gas chromatograph-mass spectrometry (SPME/GC-MS) and sugars, organic acids, and phenolic compounds with high performance liquid chromatography. Organic acids and phenolic compounds were detected with mass spectrometer (HPLC/MS). Both nitrogen and calcium fertilisation had altered sugars, organic acids, volatile and phenolic contents in strawberry fruits. Fertilisation with higher doses of nitrogen and calcium increased the content of unpleasant aromas aldehydes hexanal (up to 3.8-fold) and (E)-2-hexen-1- (up to 3.7-fold). The content of fruity esters was uppermost in fruits fertilised with nano-fertiliser Lithovit (up to 2.3-fold). Fertilisation with N and Ca decreased the strength of ketone and terpenoids fruity aroma. The highest content of total phenols, as well as all individual hydroxycinnamic and hydroxybenzoic acid derivatives were obtained in the nano-fertiliser Lithovit treatment. Fertilisation, especially with nitrogen, had mostly negative impact on strawberry flavour while nano-fertilization with Lithovit improved strawberry phenolic content and aroma.